2018
DOI: 10.1002/bin.1645
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of physical guidance procedures in the treatment of food selectivity

Abstract: In some cases of pediatric feeding disorders, reinforcementbased behavioral interventions are ineffective at increasing acceptance of target foods, and the child will not allow the feeder to deposit the bite in the mouth. A small body of research suggests that this barrier can be overcome using physical guidance procedures. The purpose of the current clinical evaluation was to extend and replicate prior research by evaluating and comparing the effects of physical guidance procedures in a home setting to treat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Per the inclusion criteria, this review only assessed articles in which experimental control was demonstrated with acceptance in at least one evaluation with a well‐defined physical guidance procedure as the primary independent variable. Therefore, some articles that mentioned a physical guidance procedure as a treatment adjunct and one article that did not demonstrate experimental control (Silbaugh et al, 2018) were not included in our assessment. Failure to include and assess these studies could overestimate actual treatment effects and strengthen the file drawer phenomenon with physical guidance research (Shadish et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Per the inclusion criteria, this review only assessed articles in which experimental control was demonstrated with acceptance in at least one evaluation with a well‐defined physical guidance procedure as the primary independent variable. Therefore, some articles that mentioned a physical guidance procedure as a treatment adjunct and one article that did not demonstrate experimental control (Silbaugh et al, 2018) were not included in our assessment. Failure to include and assess these studies could overestimate actual treatment effects and strengthen the file drawer phenomenon with physical guidance research (Shadish et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This review suggests the designations of “food refusal” or “food selectivity” do not predict the impact of care. Whereas children exhibiting refusal and receiving their calories through enteral tube feedings responded to the procedure in some studies (e.g., Patel et al, 2007; Patel et al, 2006), some participants exhibiting selectivity did not to respond to high-probability sequencing or more intensive supports (Silbaugh & Swinnea, 2018; Silbaugh, Swinnea, & Falcomata, 2018). This may reflect the imprecision of the food selectivity assignation.…”
Section: Discussionmentioning
confidence: 99%